Desain Buku Interaktif Cerita Rakyat “Malin Kundang” untuk Anak Berusia 5-7 Tahun - Lomempow, Astrid; Vdaya, Juniar (BHAGIRUPA, 2022)
Indonesia is a country filled with culture, including folktales. There are a lot of ways to preserve folktales, and one of them is story books. Through story books, moral values from the stories can flow and reach a lot of people, more importantly the children. Not only that, in 2018 it is said that story books placed on top of the books sellings in Indonesia. This fact brings a new topic, which is reading interest problems in Indonesia. This led to the title of this thesis being “Interactive storybook design of Malin Kundang for children between 5-7 years old” with formulation of the problems includes whether or not interactive storybooks could increase children’s reading interest and can illustrations give impact on children's reading comprehension. This is a qualitative based research, with its main data obtained from interviews and complimentary datas from questionnaire. Main subject for this research are the representatives of the children within the age of 5-7. Based on the obtained datas, it could be assumed that children prefer storybooks with more visuals than text, the folktales Malin Kundang is the most known and fathomed title by children. Therefore this design process is going to use the story Malin Kundang as the representative for the Indonesian folktales, because of its moral values approved and recommended for children by their representatives, and also that this title is a well known story. And the book itself is planned to be an interactive storybook to pique children’s interests.